Hubungan Mekanisme Koping dengan Tingkat Kecemasan pada Pasien Gagal Ginjal Kronik yang Menjalani Terapi Hemodialisa di RS Permata Medika Semarang - Aini, Dwi Nur; Wirawati, Maulidta Karunianingtyas; Noor, Mohammad Arifin; Ramadhani, Desi; Azkanni’am, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2024)
Hemodialysis is carried out with the help of a dialyzer machine, where hemodialysis can reduce the risk of damage to vital organs due to the accumulation of toxic substances. The hemodialysis process is carried out permanently throughout the patient's life, usually 3 to 4 hours of treatment 2 days a week (Umami et al., 2019). Chronic kidney failure patients who undergo hemodialysis therapy for a long period of time will experience various physical and psychosocial problems. Psychosocial problems faced include anxiety, depression, social isolation, loneliness, helplessness and hopelessness. Chronic kidney failure patients undergoing hemodialysis therapy must have adaptive coping mechanisms to deal with anxiety. (Siwi et al., 2020). The aim of this study was to determine the relationship between coping mechanisms and the level of depression in chronic kidney failure patients undergoing hemodialysis at Permata Medika Hospital Semarang. This type of research uses correlative descriptive with a sample size of 30 respondents using a purposive sampling technique. This research was conducted in the hemodialysis room at Permata Medika Hospital, Semarang. Based on the results of the Spearman Rank statistical test, a P value of 0.009 was obtained (P value <? (0.05)), which means that Ho was rejected and Ha was accepted, which means that there is a relationship between coping mechanisms and anxiety levels in chronic kidney failure patients undergoing hemodialysis in Permata Medika Hospital Semarang